The Analysis of Composition and Economic Value of Fish Catches at PPN Brondong: A Study Based on Species Data and Market Prices in 2024: Analisis Komposisi dan Nilai Ekonomi Hasil Tangkapan Ikan di PPN Brondong : Studi Berbasis Data Spesies dan Harga Pasar Tahun 2024 - Anwar, Muhammad Khoirul; Hidayat, Nadranabila Intani; Oka Bayu Pratama; Putri Asfarina Ifada; Suciyono (Universitas Sam Ratulangi, 2025)
This study aims to analyze the species composition and economic value of fish catches at the Nusantara Fisheries Port (PPN) Brondong in 2024. Using a descriptive-quantitative approach based on primary data, monthly data were collected on species type, catch volume, and market price over the course of one year. The results show that 35 fish species were recorded, with Swanggi, Kurisi, and Biji Nangka dominating in terms of volume, while squid contributed the highest economic value due to its high market price. On the other hand, Lemuru, Kembung, and Bawal Hitam had the lowest catch volumes and economic contributions. A discrepancy was found between catch volume and economic value, highlighting the potential for fisheries management to focus on high-value species that are currently underexploited, such as Red Snapper and Spanish Mackerel. This study emphasizes the importance of sustainable fisheries management by integrating ecological and economic considerations to ensure the long-term sustainability of marine resources and the welfare of fishing communities.